Jordan Now : New Work Opportunities for Women - Vishwanath, Tara; Krishnan, Nandini (World Bank, Washington, DC, 2012)
Improving women's access to economic opportunities remains an important development challenge for the Middle East and North Africa region (MENA). Although impressive strides have been made region-wide in improving women's educational and health outcomes, the region's low female labor force participation rates are not commensurate with these achievements. The youth, especially young women, are very vulnerable, facing significantly higher rates of unemployment. Productive use of this increasingly well educated portion of the labor force promises faster and more sustained economic growth for the region as a whole. In this context, MENA countries are looking at various policies and programs to change this situation. This quick note looks at a pilot program in Jordan which is attempting to tackle this challenge.